Defect-related electroluminescence from metal-oxide-semiconductor devices with ZrO2 films on silicon. (November 2016) - Lv, Chunyan; Zhu, Chen; Wang, Canxing; Li, Dongsheng; Ma, Xiangyang; Yang, Deren
Abstract: Defect-related electroluminescence (EL) from ZrO2 films annealed under different atmosphere has been realized by means of electrical pumping scheme of metal-oxide-semiconductor (MOS) devices. At the same injection current, the acquired EL from the MOS device with the vacuum-annealed ZrO2 film is much stronger than that from the counterpart with the oxygen-annealed ZrO2 film. This is because the vacuum-annealed ZrO2 film contains more oxygen vacancies and Zr 3+ ions. Analysis on the current-voltage characteristic of the ZrO2 -based MOS devices indicates the P-F conduction mechanism dominates the electron transportation at the EL-enabling voltages under forward bias. It is tentatively proposed that the recombination of the electrons trapped in multiple oxygen-vacancy-related states with the holes in the defect level pertaining to Zr 3+ ions brings about the EL emissions. Highlights: Defect-related EL has been realized from MOS devices with the ZrO2 films. The EL from the device with vacuum-annealed ZrO2 film is much stronger. The vacuum-annealed ZrO2 film contains more oxygen vacancies and Zr 3+ . P-F conduction dominates the electron transportation at the EL-enabling voltages. The mechanism for the EL from the ZrO2 -based MOS devices is tentatively proposed.